Problem face by bus company merger at Intrakota Consolidated Berhad / Ariff Jamili Miskon - Haji Miskon, Ariff Jamili (1995)
As an introduction to the research being done, Chapter 1 is an overview of the current situation of the subject. This chapter outlines the problem statement of the research. Generally, this chapter also provides some information about the company, Intrakota Consolidated Berhad, which the researcher refers during the research. Chapter 2 in this thesis discusses on the methodology of the research. Continuing in giving the big picture of the research, the chapter also mention the importance and the purpose of the research. As the time duration of the research is short and limited, this chapter also defines the scope and limitations of the research. Chapter 3 provides literature studies done in association to the research made. It is done in a way that the researcher tries to relate the available literature with the environment face by ICB. In Chapter 4 is the presentation of the data collected for the research. As a supplementary, charts and figures were produced in this chapter based on the data collected. The information are then analysed as to elaborate on the problems face during the merger program. Chapter 5 closes the discussions by concluding the problems that correlates the merger program. This chapter also recommend several options available for the merger company towards undertaking the task of post-merger.